The optimization of friction stir welding process parameters to achieve maximum tensile strength in polyethylene sheets - BOZKURT, YAHYA (ELSEVIER SCI LTD, 2012)
The weld strength of thermoplastics, such as high density polyethylene and polyprophylene sheets are influenced by friction stir welding parameters. The determination of the welding parameters plays an important role for the weld strength. For the influential use of the thermoplastics joints, the weld should have adequate strength. The quality of the joint was evaluated by examining the characteristics of the joint efficiency as a result of ultimate tensile strength. In this study, the Taguchi approach of parameter design was used as a statistical design of experiment technique to set the optimal welding parameters. The experiments were arranged by using Taguchi's L9 orthogonal array. The signal-to-noise ratio and the analysis of variance were utilized to obtain the influence of the friction stir welding parameters on the weld strength. Finally, the results were confirmed by further experiments. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: MECHANICAL-PROPERTIES; ALUMINUM-ALLOYS; STAINLESS-STEEL; TAGUCHI METHOD; MICROSTRUCTURE; COMPOSITE; TOOL